Visual Cryptography: Models, Issues, Applications and New Directions - D’Arco, Paolo; De Prisco, Roberto (Innovative Security Solutions for Information Technology and Communications, 2016)
Since its introduction, visual cryptography has received considerable attention within the cryptographic community. In this paper we give a quick look at the salient moments of its history, focusing on the main models, on open issues, on its applications and on some prospectives.